Information System Management for Student Discipline Based on the Attitude Record Application in an Elementary School - Badrudin, Badrudin; Muhyi, Ujang Abdul (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study examined the evolution of Management Information Systems (MIS) within the context of industry 4.0 era, specifically emphasizing student discipline management. The research aimed to implement the